cDNA expressed sequence tags of Trypanosoma brucei rhodesiense provide new insights into the biology of the parasite - Najib M. El‐Sayed; Alarcon, Clara M.; Beck, John C.; Sheffield, Val C.; Donelson, John E. (Molecular and Biochemical ParasitologyMolecular and Biochemical Parasitology, 1995)
A total of 518 expressed sequence tags (ESTs) have been generated from clones randomly selected from a cDNA library and a spliced leader sub-library of a Trypanosoma brucei rhodesiense bloodstream clone. 205 (39%) of the clones were identified based on matches to 113 unique genes in the public databases. Of these, 71 cDNAs display significant similarities to genes in unrelated organisms encoding metabolic enzymes, signal transduction proteins, transcription factors, ribosomal proteins, histones, a proliferation-associated protein and thimet oligopeptidase, among others. 313 of the cDNAs are not related to any other sequences in the databases. These cDNA ESTs provide new avenues of research for exploring both the novel trypanosome-specific genes and the genome organization of this parasite, as well as a resource for identifying trypanosome homologs to genes expressed in other organisms.
Keywords: cDNA; Expressed sequence tag; Trypanosoma brucei rhodesiense